The Image of "DOPPI" in Uzbek Folk Songs Regional Species - Golibovna, Shomurodova Sunbula (European Journal of Life Safety and Stability (2660-9630), 2021)
In this article, the image of the doppi(headdress)in Uzbek folk songs is classified by region. In Uzbek folk songs, the image of the headdress, which is considered to be one of the hats, attracts attention with its tradition and appearance as a stable symbolic image. In folk songs, they are associated with everyday life in a real and symbolic sense. This article analyzes several regional types of Uzbek headdresses based on examples.